MMF/MPA Is the Main Mediator of a Delayed Humoral Response With Reduced Antibody Decline in Kidney Transplant Recipients After SARS-CoV-2 mRNA Vaccination - Stumpf, Julian; Siepmann, Torsten; Schwöbel, Jörg; Glombig, Grit; Paliege, Alexander; Steglich, Anne; Gembardt, Florian; Kessel, Friederike; Kröger, Hannah; Arndt, Patrick; Sradnick, Jan; Frank, Kerstin; et al. (Frontiers in Medicine, 2022)
Kidney transplant recipients (KTR) show significantly lower seroconversion rates after SARS-CoV-2 mRNA vaccination compared to dialysis patients. MMF/MPA in particular has been identified as a risk factor for seroconversion failure. While the majority of all KTR worldwide receive MMF/MPA for immunosuppressive therapy, its impact on antibody decline in seroconverted KTR still remains unclear. In an observational study (NCT04799808) we investigated whether 132 seroconverted KTR (anti-SpikeS1 IgG or IgA positive after 2 vaccinations) show a more rapid antibody decline with MMF/MPA than those without this medication. Two months after mRNA vaccination, average anti-spikeS1 IgG levels of KTR with MMF/MPA were lower than without (p=0.001), while no differences between these two groups were observed after six months (p=0.366). Similar results were obtained for anti-RBD IgG antibodies (T2 p=0.003 and T3 p=0.135). The probability of severe IgG decline with MMF/MPA was three times lower than without (p = 0.003, OR 0.236, 95% CI 0.091-0.609). In the multivariate analysis, no other immunosuppressant such as calcineurin inhibitors, mTOR inhibitors or glucocorticoids, nor vaccine type, sex or age showed a significant influence on IgG titer decline between two and six months. For the decision of additional booster vaccinations, we consider immunosurveillance to be needed as an integral part of renal transplant follow-up after SARS-CoV-2 mRNA vaccination. Not only the lack of seroconversion but also the peak and titer decline of the specific IgG and RBD IgG antibody formation after two mRNA vaccinations is significantly influenced by MMF/MPA.